Sustainable Agriculture: Dukungan Pemerintah Desa Terhadap Kebijakan Pangan dan Kemandirian Petani di Kabupaten Sumenep - Rahman, Sindi Arista; Zarnuji, Zarnuji; Rasaili, Wilda; Hopid, Hopid; Wahyuni, Purwati Ratna (Universitas Galuh, 2026)
Sustainable agriculture is an important pillar in achieving national food security, especially in rural areas that have an agricultural production base. This study aims to analyse the role and support of village governments in food policy and its implications for farmer independence in Sumenep Regency. This study uses a descriptive-qualitative approach with data collection through in-depth interviews, surveys of 15 respondents, and analysis of village policy documents in five sub-districts that are agricultural production centres (Gapura, Runaru, Batang Batang, Lenteng, and Guluk-Guluk). The results show that 73% of villages have allocated Village Funds for food security programmes, particularly for the procurement of high-quality local seeds, organic fertilisers, and simple agricultural equipment. A total of 35% of villages have Village Food Security Regulations as a legal instrument to protect land and strengthen local food reserves. In addition, several farmers have begun to adopt environmentally friendly agricultural practices and crop diversification, which has resulted in an increase in income of 5–15% per planting season. Farmers' high social capital strengthens local institutional collaboration, such as Poktan, Gapoktan, and BUMDes agriculture. These findings indicate that village government support plays a significant role in strengthening farmer independence and local food security through policy, institutions, and community participation. However, challenges such as limited access to capital, dependence on aid, and land conversion still require cross-level policy intervention. This study emphasises the importance of a multi-level governance approach and community-based sustainable agriculture as strategies for strengthening village food sovereignty.